Sharon Van Etten & The Attachment Theory [compact disc] - Van Etten, Sharon; Van Etten, Sharon (Jagjaguwar, 2025)
Writing and recording in total collaboration with her band for the first time, Van Etten finds the freedom that comes by letting go. The result of that liberation is an exhilarating new dimension of sound and songwriting. The themes are timeless, classic Sharon - life and living, love and being loved - but the sounds are new, wholly realized and sharp as glass.